211k views
2 votes
I got to the final step where I need to simplify the expression but I don’t know how to

I got to the final step where I need to simplify the expression but I don’t know how-example-1
User Coltin
by
4.8k points

1 Answer

5 votes

The simplify an expression as a frection, we need to find eqaul terms in the nominator and denominator, to cancell them. The idea is, if we have a number called n, and a expression like:


(nx)/(ny)

We can divide n by n in order to get a simplifyed expression.

In this case we have:


(d)/(dx)((-4x^2+16)/((x^2+4)^2))=((x^2+4)^2\cdot(-8x)-4x(x^2+4)(-4x+16))/((x^2+4)^4)

We can see that the term (x² + 4) is repeated in the numerator and denominator. To do this easier, let's separate this in a sum of fractions:


((x^2+4)^2\cdot(-8x)-4x(x^2+4)(-4x+16))/((x^2+4)^4)=((x^2+4)^2\cdot(-8x))/((x^2+4)^4)-(4x(x^2+4)(-4x+16))/((x^2+4)^4)

Now it's much easier to cancell the repeated terms:

In the first fraction, we have the parentheses squared in the numerator and power of 4 in the denominator, to divide it, we can use the power propierties:


(a^n)/(a^m)=a^(n-m)

Then:


((x^2+4)^2)/((x^2+4)^4)=(x^2+4)^(2-4)=(x^2+4)^(-2)=(1)/((x^2+4)^2)

And now the first fraction is:


((x^2+4)^2\cdot(-8x))/((x^2+4)^4)=(1)/((x^2+4)^2)\cdot(-8x)=-(8x)/((x^2+4)^2)

For the second fraction is very similar:


(4x(x^2+4)(-4x+16))/((x^2+4)^4)

We have the same term (x² + 4) , in the numerator and denominator. Then divide:


((x^2+4))/((x^2+4)^4)=(x^2+4)^(1-4)=(x^2+4)^(-3)=(1)/((x^2+4)^3)

Then the second fraction is:


4x(-4x+16)\cdot(1)/((x^2+4)^3)=(4x(-4x^2+16))/((x^2+4)^3)

Now we can add the two fraction to get the final asnwer:


(d)/(dx)((-4x^2+16)/((x^2+4)^2))=-(8x)/((x^2+4)^2)-(4x(-4x^2+16))/((x^2+4)^3)

And that's all the simplifying we can do with this derivative

If we look at the second fraction, we have a difference of squares:


(16-4x^2)=(4^2-2x^2)

Thus:


(4^2-2x^2)=(4-2x)(4+2x)

User Stefan De Laet
by
4.8k points